Schleiermacher's Critique of Ethical Reason: Toward a Systematic Ethics - Wallhausser, John (Journal of religious ethics, 1989)
Present in Schleiermacher's early "Outlines of a Critique of Previous Ethical Theories" are major themes regarding ethics which are developed more fully in his later writings. These themes include a division of ethical reflection into three parts: foundational principles (basic ontological and anthropological assumptions), ideas (the highest good, virtue, and duty), and concepts (ethics as systematic inquiry). The essay explores these three themes to explicate Schleiermacher's thought at the time of writing the "Critique" and to show its relation to the subsequent development of his ethics.